The Structural Attributes of Gombe Lineaments in relation to Baryte-Fluorite mineralization in the Gongola Sub-Basin of the Northern Benue Trough, Nigeria: A Study Using Remote Sensing Data - D. Auwalu; A. I. Haruna; A. S. Maigari; T. P. Bata; U. Abubakar; A. Yusuf; A. Sulaiman (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
The study focuses on the Gombe Inlier, one of the significant geological features in Nigeria located within the Northern Benue Trough. It aims to provide comprehensive insights into microstructures, particularly examining the correlations between lineaments and faults in both Basement and adjacent sedimentary rocks using remote sensing data. Digital image processing techniques were applied to Landsat-08 OLI and SRTM data for lineament extraction. Field mapping revealed predominance of Basement Complex rocks, including Granite Gneiss and Pegmatite, alongside Cretaceous Sedimentary Formations. Notable Formations from the Gongola sub-basin include the Bima, Yolde, Pindiga Formations, and Gombe Sandstones. Baryte and Fluorite deposits have been identified within the research region occurring inform of fracture filling deposits hosted within Granites Gneiss and Sandstones. Geological features such as Faults, Joints, and Veins exhibit structural trends in NE-SW and NW-SE directions, with the presence of the Gombe and Wuro Ladde-Wurin Dole sinistral strike-slip faults which control the mineralization. Satellite imagery analysis identified lineament trends, with NE-SW aligned lineaments denser in Basement rocks. These lineaments (Gombe lineaments) coincide with significant fault zones in Gombe Inlier, suggesting a common tectonic origin. Fracturing patterns in Gombe inlier influence mineralizing fluid movement and controls the mineralization potentials as well as groundwater infiltration in the study area, also posing a risk for engineering constructions due to potential slope failure.